Comparison of intraoperative blood loss in piezoelectric vs. conventional technique surgeries: a systematic review and meta-analysis - Ahmadi, Sina; Rajaei, Sahar; Alimohammadi, Farnoosh; Ghaderi, Parastoo; Mokhtari, Melika; Tu, Junbo; Na, Sijia (Frontiers in Oral Health, 2025)
Background and aimOrthognathic surgeries often involve significant blood loss due to the high vascularity of the maxillofacial region. Conventional tools such as saws and burrs, while effective, can cause tissue damage and heat that may delay healing. Piezosurgery, a newer technique using ultrasonic vibrations, allows for precise bone cutting while protecting the soft tissues and nerves. This review aimed to compare intraoperative blood loss between piezosurgery and conventional osteotomy methods.Materials and methodsA systematic search of PubMed, Scopus, and Web of Science was conducted up to 5 October 2025, following the Preferred Reporting Items for Systematic reviews and Meta-Analyses guidelines. Studies involving patients who underwent orthognathic surgery using either piezosurgery or conventional tools, with reported blood loss data, were included. Six studies with 144 participants and 252 surgeries met the criteria. The data were analyzed using STATA 18 to calculate the weighted mean difference (WMD). Heterogeneity was assessed, and publication bias was evaluated with funnel plots.ResultsPiezosurgery significantly reduced blood loss compared to conventional methods, with a WMD of −81.73 mL (95% CI: −97.30 to −66.16, P < 0.001). The sensitivity analysis confirmed the reliability of these results, and formal statistical tests indicated no significant publication bias.ConclusionPiezosurgery significantly reduces intraoperative blood loss during orthognathic surgeries, likely due to its precision and minimal tissue damage. Although it is more costly and takes longer, it offers a safer alternative, particularly in complex cases. Further research with larger samples is needed to confirm these findings.Systematic Review RegistrationPROSPERO CRD420251232995.